Application of google sites assisted problem based learning model to junior high school students' mathematical problem solving ability - Jusra, Hella; Nuranggraeni, Dita (Desimal: Jurnal Matematika, 2023)
Students have the ability to solve difficulties that are perceived as inadequate; efforts are required to continue to enhance them. There is an idea that the main goal of learning mathematics is to produce students who can solve problems competently. Thus, the purpose of this study is to see if there is an effect of employing a problem-based learning paradigm aided by Google Sites on the mathematical problem-solving abilities of junior high school students. A quantitative experiment with a quasi-experimental design was employed as the research method. The sample approach used is non-probability sampling of the purposive sampling variety. The instruments used have been tested for validity and reliability. The data analysis technique uses prerequisite analysis tests, namely normality and homogeneity tests. Initial hypothesis testing was carried out using the Mann-Whitney U Test. The results of the study show that problem-based learning with Google Sites has an impact on the mathematical problem-solving abilities of junior high school students.